Investigating psychometric properties of the arm activity measure – Thai version (ArmA-TH) sub‐scales using the Rasch model - Buntragulpoontawee, Montana (BMC Med Res Methodol, 2021)
BACKGROUND: This study investigated the ArmA-TH sub-scale measurement properties based on item response theory using the Rasch model. METHODS: Patients with upper limb hemiplegia resulting from cerebrovascular and other brain disorders were asked to complete the ArmA-TH questionnaire. Rasch analysis was performed to test how well the ArmA-TH passive and active function sub-scales fit the Rasch model by investigating unidimensionality, response category functioning, reliability of person and item, and differential item functioning (DIF) for age, sex, and education. RESULTS: Participants had stroke or other acquired brain injury (n = 185), and the majority were men (126, 68.1 %), with a mean age of 55 (SD 22). Most patients (91, 49.2 %) had graduated from elementary/primary school. For the ArmA-TH passive function scale, all items had acceptable fit statistics. The scale’s unidimensionality and local independence were supported. The reliability was acceptable. A disordered threshold was found for five items, and none indicated DIF. For the ArmA-TH active function scale, one item was misfit and three were locally dependent. The reliability was good. No items showed DIF. All items had disordered thresholds, and the data fitted the Rasch model better after rescoring. CONCLUSIONS: Both sub-scales of ArmA-TH fitted the Rasch model and were valid and reliable. The disordered thresholds should be further investigated.